Cycle variation of Coronal Bright Points (CBPs) number from EIT/SOHO data - Sattarov, I.; Karachik, N.V.; Tillaboev, A.M.; Sherdanov, Ch.T. (Известия Крымской астрофизической обсерватории, 2009)
Temporal variations of coronal bright points number in EIT/SoHO data from 195 pass band for 1996−2008 are studied. For identification of CBPs the method developed by authors is used. It is found that: cycle variation of CBPs number is complete by July 2008; cycle variations of CBPs number are different at different latitudes.